2018
DOI: 10.1101/493320
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Maladaptive coping strategies and neuroticism mediate the relationship between 5HTT-LPR polymorphisms and symptoms of anxiety in elite athletes.

Abstract: Previous studies have suggested that genetic factors, personality traits and coping strategies might play independent and interacting roles in influencing stress-related anxiety symptoms. The aim of this study was to examine whether Neuroticism and maladaptive coping strategies mediate the association between the serotonin transporter gene-linked polymorphic region (5HTT-LPR) and symptoms of anxiety and depression in elite athletes who experience high levels of competitive stress. One hundred and thirty-three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 85 publications
1
11
0
Order By: Relevance
“…Several recent epidemiological studies have demonstrated a correlation between urinary BPA levels and obesity ( 55 , 56 ). Moreover, as previously described, the exposure to BPA can induce adverse effects on neurological control, suggesting an involvement in behavior management ( 57 59 ). A very recent study performed on obese subjects demonstrated a reduction in most phthalate levels after a dietary intervention ( 60 ).…”
Section: Discussionsupporting
confidence: 62%
“…Several recent epidemiological studies have demonstrated a correlation between urinary BPA levels and obesity ( 55 , 56 ). Moreover, as previously described, the exposure to BPA can induce adverse effects on neurological control, suggesting an involvement in behavior management ( 57 59 ). A very recent study performed on obese subjects demonstrated a reduction in most phthalate levels after a dietary intervention ( 60 ).…”
Section: Discussionsupporting
confidence: 62%
“…Thus, the present results can be complemented by integrating skill constructs, fitness constructs and to shed light on the relative importance of archery performance factors and guide the training practice process. Besides, recent studies have also suggested that genetic polymorphisms are associated with athletes’ emotional control ( Altamura et al, 2019 ) and sport performance ( Ahmetov et al, 2016 ), and therefore, the inclusion of genetic polymorphism structure in the model could be considered and guide the athlete selection.…”
Section: Discussionmentioning
confidence: 99%
“…These elements, in turn, expose users to the risk of developing a substance abuse disease. In this regard, it can be very useful to analyze the relationship between genetic predisposition for stress management and AAS use/abuse [89,90]. In other words, further studies are needed to highlight the possible relationship between the subject with a negative genetic predisposition to stress management and AAS abuser.…”
Section: Discussionmentioning
confidence: 99%